Let's denote the first term of the arithmetic progression by 'a' and the common difference by 'd'.
From the given information, we can set up two equations:
6th term: a + 5d = 20
11th term: a + 10d = -5
We have a system of two equations with two variables, so we can solve it to find the values of 'a' and 'd'.
Subtracting the first equation from the second equation, we get:
(a + 10d) - (a + 5d) = -5 - 20
5d = -25
d = -5
Substituting this value into the first equation, we get:
a + 5(-5) = 20
a - 25 = 20
a = 20 + 25
a = 45
Therefore, the first term 'a' is 45 and the common difference 'd' is -5.
Now, we can find the sum of the first three terms by substituting these values back into the arithmetic progression formula:
Sum of the first three terms = (3/2) * [2a + (n-1)d] [where n is the number of terms]
= (3/2) * [2(45) + (3-1)(-5)]
= (3/2) * [90 + 2(-5)]
= (3/2) * [90 - 10]
= (3/2) * 80
= 120
Therefore, the sum of the first three terms is 120.
The 6th term of an arithmetic progression is 20 and the 11th term is -5. Find the sum of the first three term
1 answer